Modelo das intenções de reserva de hospedagem via aplicativos de redes sociais - Gondim, Cibelle Batista (2022)
The increasing use of mobile devices and the improvement in the development of social media platforms have brought significant changes to the travel planning process and to e-commerce in tourism. Mobile social commerce resulted from the evolution of traditional electronic commerce, which started to incorporate functions of socialization and exchange of information between users, concomitantly to the adaptation of commercial transactions to mobile devices. The main objective of this thesis was to develop a theoretical model that brings together the factors that influence the intention to book accommodation through social network applications. The model developed had as its initial theoretical basis the Theory of Planned Behavior. Variables from four other theories were added to the constructs of that theory, namely: perceived general risk (Perceived Risk Theory), reputation of the social network platform (Signaling Theory), perceived relative advantage (Diffusion of Innovations Theory) and perceived social support (Social Support Theory). The variables included in the model refer to characteristics of social network applications. The research sampling was nonprobabilistic. In total, 486 valid questionnaires were analyzed, applied online to Brazilian consumers who use social networking applications. The research with a quantitative approach, and characterized as descriptive, correlational, and explanatory, adopted the technique of modeling structural equations by partial least squares for the analysis and treatment of data. The software used to analyze the model was SmartPLS 3 (version 3.3.9). Among ten hypotheses established, nine were supported. The model achieved substantial explanatory power, being able to explain 75.8% (R² = 0.758) of booking intentions in the analyzed context. Regarding the intention to book construct, among the four independent variables proposed in the model as related to it, it was found that attitude was the most influential and significant, mediating (totally or partially) other established relationships. The favorable attitude of consumers obtained in the model an explanatory value of 70.1% (R² = 0.701). Among the relationships of influence on attitude, the perceived relative advantage proved to be the most representative, despite its moderate effect. This perception of the relative advantage of social media apps as accommodation booking channels, compared to other available options, resulted in the investigation of aspects such as perceived pleasure, perceived financial advantage, convenience, and personalized ads, respectively. It was noted that the opinion of third parties (or subjective norms) on the use of social networking applications in the context studied demonstrated a reasonable influence on both attitude and intention to book. On the other hand, perceived behavioral control showed a positive and insignificant influence on consumers' attitude. The relationship established between the general perceived risk and the attitude proved to be negative and insignificant. Among the types of risks observed in the context of consumption in social network applications, privacy and security, psychological and financial risks stood out. It was found that the perception of a good reputation of the social network platform attested to having an indirect and negligible effect on the intention to book accommodation through the mediation of attitude. Although the hypothesis of a direct relationship between perceived social support and intention to book has not been confirmed, this construct has been shown to have an influence through the mediation of subjective norms and attitude. It should be noted, however, that this effect was negligible. It was possible to verify that informational support, emotional support, and platform support were significant for the respondents' perception of general social support, in that order. In turn, this perceived general support had a moderate influence on the social pressure felt by them (subjective norms) regarding the possibility of using social network applications to book accommodation. From the analysis of the results, the study brought theoretical and practical contributions to researchers in the field of tourism and hospitality, to managers of accommodation companies, and to the platforms that manage social network applications.